Four-year survival rate in pulmonary sarcoidosis with extensive pulmonary hypertension screening. (April 2022) - Huitema, M.P.; Mathijssen, H.; Bakker, A.L.M.; Mager, J.J.; van Houten, L.; Grutters, J.C.; Post, M.C.
Abstract: Background: Sarcoidosis is a systemic disease of unknown aetiology with significant morbidity and mortality. The PULSAR study prospectively performed cardiac analysis including systematic pulmonary hypertension screening in sarcoidosis patients newly referred to a tertiary sarcoidosis center. In this manuscript we studied the four-year mortality of this population. Methods and main findings: Between august 2015 and October 2017, 399 patients (58% male, mean age 49.4 years, 90.5% Caucasian) were included and followed for a mean period of 4.3±0.7 years. In total, 10 patients had died at the time of analysis . 1-, 2-, 3- and 4-year survival rate was 100% (n=399), 99.0% (n=399), 98.2% (n=399) and 94.6% (n=276). Most patients died of respiratory failure, other causes were heterogeneous including cardiac, neurological and non-sarcoidosis origin. A low CPI score or modified Walsh score was associated with higher mortality, similar for high PH probability on echocardiography and elevated right ventricular systolic pressure. Conclusion: This study highlights that elevated RVSP and presence of PH on echocardiography and progression of fibrotic disease with subsequent decline in pulmonary function test are important factors for mortality in sarcoidosis patients. Highlights: er4-year survival in patients with pulmonary sarcoidosis patients referred to a tertiary centre was 94.6%. Signs of PH on echo, severe fibrotic disease and decline in pulmonary function test are important factors for mortality. The cause of mortality in pulmonary sarcoidosis is heterogeneous including pulmonary, cardiovascular and neurologic causes.